Association of heavy metals exposure with lower blood pressure in the population aged 8–17 years: a cross-sectional study based on NHANES - Liang, Yongzhou; Zhang, Minjie; Jin, Wenhao; Zhao, Liqing; Wu, Yurong (Frontiers in Public Health, 2024)
The existing evidence regarding the joint effect of heavy metals on blood pressure (BP) in children and adolescents is insufficient. Furthermore, the impact of factors such as body weight, fish consumption, and age on their association remains unclear.The study utilized original data from the National Health and Nutrition Examination Survey, encompassing 2,224 children and adolescents with complete information on 12 urinary metals (barium, cadmium, cobalt, cesium, molybdenum, lead, antimony, thallium, tungsten, uranium, mercury and arsenic), BP, and core covariates. Various statistical methods, including weighted multiple logistic regression, linear regression, and Weighted Quantile Sum regression (WQS), were employed to evaluate the impact of mixed metal exposure on BP. Sensitivity analysis was conducted to confirm the primary analytical findings.The findings revealed that children and adolescents with low-level exposure to lead (0.40 μg/L, 95%CI: 0.37,0.42), mercury (0.38 μg/L, 95%CI: 0.35, 0.42) and molybdenum (73.66 μg/L, 95%CI: 70.65, 76.66) exhibited reduced systolic blood pressure (SBP) and diastolic blood pressure (DBP). Conversely, barium (2.39 μg/L, 95%CI: 2.25, 2.54) showed a positive association with increased SBP. A 25th percentile increase in the WQS index is significantly associated with a decrease in SBP of 0.67 mmHg (95%CI: -1.24, -0.10) and a decrease in DBP of 0.59 mmHg (95% CI: -1.06, -0.12), which remains statistically significant even after adjusting for weight. Furthermore, among individuals who consume fish, heavy metals have a more significant influence on SBP. A 25 percentile increase in the WQS index is significantly associated with a decrease of 3.30mmHg (95% CI: -4.73, -1.87) in SBP, primarily attributed to mercury (27.61%), cadmium (27.49%), cesium (17.98%), thallium (8.49%). The study also identified a declining trend in SBP among children aged 10-17, whereas children aged 11-18 exhibited lower levels of systolic and diastolic blood pressure, along with a reduced risk of hypertension.Some heavy metals demonstrate an inverse association with the BP of children and adolescents, particularly notable in groups with fish consumption and older children and adolescents. Future studies are warranted to validate these findings and delve deeper into the interplay of heavy metals.